Duration limits for exposure for the whole body and extremities with a military extreme cold protection clothing ensemble at an ambient temperature of -40°C. Issue 2 (3rd April 2022) - Cartwright, Jacob M.T.; Etter, Clara V.; Gnatiuk, Elizabeth A.; Perrotta, Andrew S.; Wang, Faming; White, Matthew D.
ABSTRACT: Manual performance and body temperature responses were assessed in a 1-h trial at an ambient temperature (TAMB ) of −40°C for 7 male participants (32 ± 14 (mean ± SD) years) wearing a typical military extreme cold protection clothing ensemble. The purpose was to establish duration limited exposure (DLIM ) for these conditions, and it was hypothesized that (i) core temperature (TCORE ) would remain normothermic, whereas extremity skin temperature (TSK ) would decrease; (ii) decrements of manual performance would be in proportion to decreases of hand TSK ; and (iii) DLIM would be determined by the hand or foot TSK responses. Linear regression was employed to assess associations of manual performance scores and body temperatures with DLIM assessed using the Required Clothing Insulation (IREQ ) model and extremity temperatures in ISO 11079–2007. Results showed TCORE remained at 37.3°C, whereas there were significant (0.0001 < p < 0.05) decreases in extremity TSK . Associations between manual performance and hand TSK showed coefficients of determination (R 2 ) ranging from 0.48 < R 2 < 0.98; 0.00005 ≤ p ≤ 0.08. The DLIM for the whole-body ensemble ranged from 2.2 h to > 8 h, whereas the DLIM for the extremities was 0.56 ± 0.20 h for TSK decreasing 15°C. In conclusion, the hypotheses of a stable core temperature and decreases of extremity skin temperature giving decrements in manual performance were accepted as was the hypothesis that duration limits for exposure would be determined by extremity skin temperatures of the hand and foot.